Myocardial functional recovery following durable ventricular assist device in children - Bhavikkumar Langanecha; Osami Honjo; Alyssa Power; Oshri Zaulan; Christoph Haller; Kristen George; Linda Fazari; Andrea Maurich; David Chiasson; Aamir Jeewa (JHLT Open)
Background: Ventricular assist device (VAD) explantation following myocardial functional recovery (MFR) for heart failure (HF) is uncommon in children and is associated with a risk of HF recurrence. Material and Methods: Retrospective, single-center study of pediatric patients who were supported with durable VADs, both intracorporeal continuous flow devices (CFD) and paracorporeal pulsatile flow devices (PFD), between 2004 and 2022. Results: A total of 74 children, of which 43 were female, underwent VAD implantation (PFD = 61 and CFD = 14) at a median (interquartile range) age of 5.6 (0.8, 13.5) years and with a weight of 16.2 (7.5, 40.7) kg. From this cohort, we identified 9 of 75 (12%) children who underwent VAD explantation for MFR. Of those, 7 of 9 (77%) were under 2 years of age and 6 of 9 (67%) were supported for >90 days. Five patients had dilated cardiomyopathy, 3 with anomalous left coronary artery from pulmonary artery and 1 with tachycardia-induced cardiomyopathy. Six were listed for transplantation as a part of their HF management strategy following VAD implantation. After explant, 8 of 9 patients remained in HF remission with no symptoms and stable left ventricular function. One patient had a recurrence of HF following explantation after demonstrating MFR while on VAD support. Conclusions: MFR resulting in VAD explantation is feasible in children with chronic HF especially for those <2 years of age. Further work is needed to better identify the features that promote MFR and maintain it after explant.